A STUDY ON THE ASPECTS OF EUROCENTRISM AND DIFFUSIONISM REPRESENTED IN FOREIGNERS’ TRAVEL RECORDS ON KOREA IN EARLY 1900s - CHO, Kang Sok (International Journal of Korean Humanities and Social Sciences, 2017)
This paper deals with three different perspectives appeared in foreign visitors’ records on Korea in 1900s. Jack London was a writer who wrote novels highly critical of American society based on progressivism. However, when his progressive perspective was adopted to report the political situation of Korea in 1904, he revealed a typical perspective of orientalism. He regarded Korea and ways of living in Korea as disgusting and ‘uncivilized.’ Compared with Jack London’s perspective, French poet Georges Ducrocq’s book was rather favorable. He visited Korea in 1901 and he showed affectionate attitude toward Korea and its people. However, his travel report, Pauvre et Douce Coree, can be defined as representing aesthetic orientalism. He tried to make all the ‘Korean things’ seem beautiful and nice, but it is true that this kind of view can also conceal something concrete and specific. This perspective at once beautifies Korea and also conceals the reality about Korea. E. Burton Holmes was a traveler and he often used his ‘motion-picture’ machine to record things he witnessed while travelling around worldwide countries. So, his report (travelogue) and motion picture film on Korea written and made in 1901 was based on close observation and rather objective point of view. Nonetheless, he couldn’t avoid the perspective of the colonizer’s model of the world, in other words, geographical diffusionism of western culture.